A Dinculear Rhenium Complex with a Proton Responsive Ligand in the Electrochemical‐Driven CO2‐Reduction Catalysis. Issue 17 (2nd May 2018) - Wilting, Alexander; Siewert, Inke
Abstract: Herein, we present a detailed study on a dinuclear Re complex bearing an α ‐diimine‐tricarbonyl motif and a proton responsive ligand in the electrochemical CO2 reduction catalysis. The complex exhibits a pyrazole‐pyridine entity as α ‐diimine unit and a phenol moiety as internal proton relay, which show non‐innocent behaviour under reductive conditions. Initial two electron reduction leads to NH bond cleavage forming the deprotonated ligand LH−2 . Further two electron reduction at considerable negative potential induces OH bond cleavage and ligand reduction. In the presence of CO2, the reduced species reacts with CO2 forming CO. The complex shows a moderate Faraday efficiency and the activity is similar to the mononuclear derivative [Re(bpy)(CO)3 (py)] + (py=pyridine, bpy=2, 2′‐bipyridine). Abstract : A dinuclear Re2 (CO)6 L complex was utilised as molecular electrocatalyst in the CO2 ‐to‐CO conversion. A detailed mechanistic study led to a comprehensive picture of the coupled chemical and electrochemical steps during catalysis.